The complete mitochondrial genome of the firefly Curtos fulvocapitalis (Coleoptera: Lampyridae) - Wei Li; Quan Liu; Xinhua Fu (Mitochondrial DNA. Part B. Resources, 2022)
We report the complete mitochondrial genome of the firefly Curtos fulvocapitalis Jeng et Yang 1998. The circular genome is 16,398 bp and has a base composition of A (42.21%), C (11.22%), G (7.73%), and T (38.85%). Our sequence is similar to those of other metazoans, which contain 13 protein-coding genes. All 13 protein-coding genes were initiated by the ATN (ATT, ATA, and ATG) codon. Nine protein-coding genes stopped with TAA or TAG codons, and the other four genes had an incomplete termination codon, a single T. We sequenced the mitochondrial genome of fireflies to analyze phylogenetic relationships and determine the evolution of their flashing signals.